Anxiety mediates the effect of social media addiction on negative attentional bias: the moderating role of impulsivity - Rui Qiu; Yushan Li; Yue Gong; Zhihua Guo; Sizhe Cheng; Mengze Li; Xia Zhu (Frontiers in Psychiatry, 2025)
ObjectiveIn China, platforms such as WeChat serve as integral hubs for communication, education, and daily life, rendering social media addiction a pressing concern among university students. Their profound digital immersion, combined with academic pressures, creates a unique contextual milieu where the cognitive ramifications of addiction, including negative attentional bias may be exacerbated. This study therefore aims to investigate the mediating role of anxiety and the moderating role of impulsivity in the relationship between social media addiction and negative attentional bias.MethodsA cross-sectional survey was conducted with 1,006 Chinese university students (81.1% male; the mean age of participants was 21.45 ± 2.013 years). Participants completed measures of social media addiction, anxiety, negative attentional bias, and impulsivity. Data were analyzed using SPSS and PROCESS macros for mediation and moderation effects with bootstrapping.ResultsSocial media addiction directly predicted negative attentional bias (β = 0.270, p < 0.001) and indirectly through anxiety (indirect effect = 0.111, 95% CI [0.073, 0.153]). Impulsivity moderated both the direct effect (β = -0.020, p < 0.001) and the anxiety-mediated pathway (β = -0.026, p < 0.001). Specifically, anxiety strongly predicted negative attentional bias at low impulsivity (β = 0.893, p < 0.001) but not at high impulsivity (β = 0.023, p = 0.730).Conclusionhis study reveals a moderated mediation model where anxiety mediates the effect of social media addiction on negative attentional bias, and impulsivity buffers this relationship. These findings highlight the importance of addressing anxiety and impulsivity in interventions for social media addiction-related cognitive biases.